SULTHAN IN THE AL-QUR’AN - Andi Rama Dhani; Linda Susanti; Hasnah - (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2022)
Allah SWT is the absolute ruler of the universe and its contents, but Allah SWT also gives a small portion of His power to His servants in different forms according to the needs of His servants. This foundation is the basis for researchers to carry out a study entitled